Innovation of MMS with inspiration from the past - Ceccarelli, Marco (Zielona Góra: Uniwersytet Zielonogórski)
This survey is a critical overview of main aspects and topics of today`s research and innovation, with specific focus on MMS, while looking at past developments and achievements through few significant examples. Thus, we can discover that most of the today`s ideas and concepts have already been explored and exploited in the past. Nevertheless, today we have the great challenge of technology that permits advanced technical results that were not possible in the past within the practical innovation that today more and more is expected from research results.
Keywords: biomechanics; elasticity; plasticity; vibrations; mechanics of structures; mechatronics; plates & shells; magnetohydrodynamics; rheology; thermodynamics; tribology; fluid dynamics